Conjunctive Use of Surface and Groundwater to Improve Food Productivity in the Dry Zone Area - Sivakumar, S. (Voice for Change-Journal of Jaffna Managers Forum, 2013)
It is observed that at present the water that is available is not utilized effectively to achieve maximum productivity in terms of food production. Food scarcity is a pressing problem in many countries of the globe. The problem is, however, particularly serious in less developed countries with low agricultural production combined with a fast growing population. To meet food requirements, efforts should be made to increase the food production, at least several times over the present supply. This can be done by the use of better viable and vigour seeds, development and cultivation of new improved crop varieties, use of proper fertilizers, pesticides, and herbicides, better on-farm water management, better use of agricultural implements, provision of extension services, strengthening of the existing institutions and introduction of new socio-economic legal and organisational support together with proper implementation of suitable alternate policy regarding the conjunctive use of surface and groundwater.